Loading capacity of wet puna pastures in a context of climate change - Estrada Zuñiga, Andrés Corsino (2018)
Floristic composition and rangeland condition of the Phynaya Peasant Community (located North of Pitumarca district and EastNorth of Canchis Province, Cusco region) were evaluated to estimate stocking rate under climate change scenario. Floristic composition, vegetation cover, and plant vigor were evaluated on 79 step-transects of 200 m in six rangeland sectors. Preliminary results reveal that there are 60 species, grouped in 13 families, where the dominant families were Poaceae (46.67%), Asteraceas (15%) and seudograsses (13.3%), of which, 45% were palatable for alpacas. Of the total grazing areas, alpacas´ areas represent 70.4%, llamas 15.4%, cattle 3.5%, sheep 4.5% y vicunas 6.3%. Actual stocking was 1 alpaca unit per hectare while stocking rate average estimated was fair with supportability of 0.78 UAl/ha; thus, rangelands are considered on degradation process